2002
DOI: 10.1186/1471-2474-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of estrogen receptor-β in annulus cells of the human intervertebral disc and the mitogenic effect of 17-β-estradiol in vitro

Abstract: Background: Recent evidence suggests that estrogens exert effects in different tissues throughout the body, and that the estrogen receptor β (ERβ) may be important for the action of estrogen (17-β-estradiol) on the skeleton. The cellular localization of ERβ in the human intervertebral disc, however, has not yet been explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 22 publications
2
41
1
1
Order By: Relevance
“…Estrogen deficiency in menopause is associated with certain changes. The intervetebral disc annulus fibrosis cells have been shown to express the estrogen beta receptor gene and culture of these cells in estradiol showed significantly increased cellular proliferation (Gruber et al, 2002). The flattening of the intervertebral discs contributes to the height loss associated with menopause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogen deficiency in menopause is associated with certain changes. The intervetebral disc annulus fibrosis cells have been shown to express the estrogen beta receptor gene and culture of these cells in estradiol showed significantly increased cellular proliferation (Gruber et al, 2002). The flattening of the intervertebral discs contributes to the height loss associated with menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral fractures resulting from osteoporosis also leads to loss of vertebral body height and in other instances kyphosis which in turn causes a decrease in stature. Consequently, excessive decrease in height in postmenopausal women is highly suggestive of the presence of osteoporotic fractures and should serve as an indication for a spinal radiograph (Kaptoge et al, 2004;Gunnes et al, 1996;Spector et al, 1993;Riggs and Melton, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposing anulus cells to 17-β-estradiol led to significantly greater proliferation than in low serum controls. The effect of estrogen on the disc cells could be related to the anti-apoptotic effect of IGF-1 on them (Gruber et al, 2002).…”
Section: The Molecular Biology Of Anulus Fibrosus Components and Theimentioning
confidence: 99%
“…The sample size used in this superiority trial was calculated on a difference in effect size of ϳ0.4 SD units between hylan and HA, derived from a meta-analysis performed in 2003 (2). However, several meta-analyses, including new controlled trials and comparison studies between viscosupplements (with conflicting results), have been published since 2003 (3)(4)(5). A recent trial (not supported by a pharmaceutical firm) demonstrated superiority of hylan compared with HA (notably in terms of duration of action) but without a huge difference in terms of the magnitude of response (5).…”
Section: To the Editormentioning
confidence: 99%